The analysis of BOT strategies based on game theory – case study on Taiwan’s high speed railway project - Chen, Tien-Chien; Lin, Yu-Cheng; Wang, Lung-Chuang (Journal of Civil Engineering and Management, 2012)
Uncertainty in a contract for some BOT (Build-Operate-Transfer) projects may allow an opportunistic developer to take advantage of information asymmetrical factors, long-term external changes, and agency dilemma to request renegotiation and to alter the contact after it has been awarded. Such requests often entrap the government in hold-up problems and result in improper payments to the developers and may even create general public dissatisfaction with a project. In this paper, the Game Theory model is used to analyze the Taiwan High Speed Railroad project to examine how developers implement different strategies at the various stages of a project to alter the contract’s conditions in order to continually creating competitive advantage after they have been awarded the contract. This project developer is now facing serious financial difficulties. In this study, the financial information on the Taiwan High Speed Railroad operations was used as the foundation for conducting a simulation to calculate the project’s value after this project began operation. The results will serve as reference to the best decision-making strategy for renegotiating costs in competition and cooperation so that a developer can select the optimum project offering the maximum reward. Also, the result will be offered to industries involved in market competition or act as an approach to establish future BOT policies on renegotiation.